Reciprocal Social Behavior and Related Social Outcomes in Individuals at Clinical High Risk for Psychosis. (December 2021) - Zou, Denise S.; Cowan, Henry R.; Azis, Matilda; Mittal, Vijay A.
Highlights: Those at clinical high risk for psychosis suffer from social difficulties Reciprocal social behavior is impaired in these individuals compared to controls RSB deficits are linked to multiple functional social outcomes Links to negative attenuated psychotic symptoms warrant further investigation Abstract: Reciprocal social behavior (RSB) deficits have been noted in formal psychotic disorders and may play a role in the clinical high-risk for psychosis (CHR) syndrome. The present study examined RSB deficits and clinical and social functioning correlates in 45 individuals meeting criteria for a CHR syndrome and 47 healthy comparisons (HC). Further, this study examined associations with number of friends, problematic social Internet use, and perceived social support. Compared to the HC group, the CHR group exhibited greater deficits in total RSB and in all RSB subdomains. Total RSB deficits were associated with greater negative but not positive symptom severity in the CHR group, and greater social functional impairment. RSB deficits also may have related to fewer friendships, more problematic social Internet use, and less perceived belonging and tangible social support, although relationships with Internet use and perceived social support did not survive FDR-correction. These findings provide further evidence that RSB is impaired in the CHR syndrome and suggest specific social outcomes that may be affected. Further investigations with larger, diverse samples and repeated measures can confirm these findings.